Geomorphological observations surrounding Lukla, eastern Nepal Himalaya - Rai, SM; Yoshida, M; Upreti, BN (Journal of Nepal Geological Society, 2008)
The geomorphological observations were carried out in the area of Lukla and its surroundings: Nachipan, Rondinma, Chaurikharkha, Muse, Nakchun, Tate and Surke villages. The Dudh Koshi River runs along N-S direction crossing these different villages. The heights of the different platforms of the different areas and river floors show the correlations of height spans with permanent or mean height of the plains (Fig. 1). The different platforms are surrounded by steep topography containing different rock types: mainly of biotitesillimanite- garnet gneiss, partly of quartzite and Miocene granite/pegmatite belonging to the Higher Himalayan Crystalline Sequence (HHCS). The different platforms contain moraine, colluviums and river terrace deposits. The Nachipan platform, located to the NNW direction from Lukla village consists of moraine, colluviums and terrace deposits. Regarding geomorphic development of the Nachipan platform following stages can be summarized: (a) Main glacier moraine sediments carried by the Dudh Koshi River were deposited. This stage of evolution is main glacial moraine stage. (b) This moraine deposit was eroded by the same river and river terraces were deposited over the moraine deposit. This stage is called as upper Nachipan terrace stage. (c) This stage was followed by earlier main landslide stage. In this stage, moraine deposit as a landslide (colluviums) covered the terrace deposit. (d) Then erosion process occurred on moraine, terrace and main landslide (colluviums) deposits by the Dudh Koshi River. Then terrace deposits were formed over moraine deposit. This stage is called as lower Nachipan terrace stage. (e) Later major landslide stage occurred. In this stage the upper Nachipan terrace, moraine and earlier landslide materials were collapsed down as a single major landslide stage. (f) Then again erosion process occurred on later major landslide stage and lowest Nachipan terrace stage was developed. (g) Finally recent river terrace deposits were formed by the Dudh Koshi River. Rondinma platform, located to the NWW direction from Lukla village consists of subrounded to rounded pebbles, cobbles and boulders carried by the Dudh Koshi valley. Chaurikharka platform, located NNW direction from the Lukla village is topographically flat and is covered by huge boulders of mainly quartzite, partly of biotite-sillimanite-garnet gneiss and granite. Below the sediments, the materials could be the continuation of Nachipan glacial moraine stage. Muse platform, located to the south of Chaurikharka platform is mainly covered by huge boulders of mainly biotite-sillimanitegarnet gneiss, with less migmatized biotite gneiss. At lower part of Muse platform, few rounded gravels are also found. Lukla platform has very gentle topography (less than 15 degree) and consists of mainly angular to sub angular colluviums and is partly by terrace sediments. Some large boulders found at the lower part of Lukla platform consist of mainly biotite-sillimanite-garnet gneiss. Similarly Tate platform, located to the W from the Lukla village has gentle topography (less than 25 degree) and contains mainly of large boulders of colluvium materials and few fluvial sediments. Therefore, different platforms contain different types of sediments: moraine, colluviums and alluvium during their development stages. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.29